2017
DOI: 10.1183/13993003.00392-2017
|View full text |Cite
|
Sign up to set email alerts
|

Airway calibre variation is a major determinant of exhaled nitric oxide's ability to capture asthma control

Abstract: @ERSpublicationsClinicians must take into account FEV1 changes when using FENO as a marker of asthma control http://ow.ly/XFmp30c4emjCite this article as: Michils A, Haccuria A, Michiels S, et al. ABSTRACT Changes in airway calibre have the potential to modify exhaled nitric oxide fraction (FENO) values and could hamper how FENO captures changes in asthma control. Here, our objective was to assess whether forced expiratory volume in 1 s (FEV1) variations alter the ability of FENO to reflect asthma control.FENO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A large part of FeNO is produced in the peripheral airways and therefore FeNO might paradoxically decrease if the small airway caliber reduces despite no changes in airway inflammation 8 . Thus, we speculate that the decrease in FeNO in the high FeNO group might be induced by small airway narrowing as reflected by the increase in R5 and R5‐R20 in this study.…”
Section: Figurementioning
confidence: 65%
“…A large part of FeNO is produced in the peripheral airways and therefore FeNO might paradoxically decrease if the small airway caliber reduces despite no changes in airway inflammation 8 . Thus, we speculate that the decrease in FeNO in the high FeNO group might be induced by small airway narrowing as reflected by the increase in R5 and R5‐R20 in this study.…”
Section: Figurementioning
confidence: 65%
“…Soto-Ramos et al found that patients with well-controlled asthma had lower FeNO levels [16] . However, Michils et al found that changes in asthma symptoms did not coincide with changes in pulmonary function and FeNO [17] . Our study found that FeNO levels differed according to the level of asthma control, with the highest level in the poor control group and a gradual decrease with improvement in asthma control.…”
Section: Discussionmentioning
confidence: 98%
“…The performance of FE NO as a biomarker of asthma control increases when its assessment is combined with lung function parameters [122][123], when it is used to predict the future risk of losing asthma control [124][125][126][127][128], or when its increase in a given time is considered as a marker of loss of asthma control [119].…”
Section: Fe No and Asthma Controlmentioning
confidence: 99%